2021
DOI: 10.1007/s00431-021-04232-7
|View full text |Cite
|
Sign up to set email alerts
|

Insufficient maternal gestational weight gain and infant neurodevelopment at 12 months of age: the Japan Environment and Children’s Study

Abstract: Abnormal maternal gestational weight gain (GWG) increases the risk of obstetric-related complications. This investigation examined the impact of GWG on infant neurodevelopmental abnormalities at 12 months of age using the data of a nationwide Japanese cohort study. Questionnaire data were obtained from the ongoing Japan Environment and Children’s Study cohort study. Maternal GWG was subdivided as below, within, or above the reference values of the Institution of Medicine pregnancy weight guidelines. The Ages a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
8
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 39 publications
1
8
0
Order By: Relevance
“…Moreover, studies have shown that insufficient weight gain is associated with a variety of adverse maternal and infant outcomes, such as an increased risk of gestational diabetes [ 20 ] and low birthweight or small-for-gestational-age offspring [ 21 , 22 , 23 ]. Babies born to women with inadequate weight gain had an increased risk of death within their first year of life [ 24 ] and slower neurodevelopment later in life [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, studies have shown that insufficient weight gain is associated with a variety of adverse maternal and infant outcomes, such as an increased risk of gestational diabetes [ 20 ] and low birthweight or small-for-gestational-age offspring [ 21 , 22 , 23 ]. Babies born to women with inadequate weight gain had an increased risk of death within their first year of life [ 24 ] and slower neurodevelopment later in life [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although we were unable to look at connections between the various cognitive domains in this study. Insufficient maternal GWG may harm an infant’s neurodevelopment, according to a large survey conducted in Japan in 2021 ( 32 ). GWG below recommended levels was linked to a significantly higher risk of developmental delay for the domains of communication (odds ratio [OR] 1.21, 95% confidence interval [CI] 1.09–1.34), gross motor (OR 1.14, 95%CI, 1.05–1.24), fine motor (OR 1.13, 95%CI, 1.04–1.24), problem-solving (OR 1.09, 95%CI, 1.01–1.18), and personal-social (OR 1.15, 95%CI, 1.08–1.25) ( 32 ).…”
Section: Discussionmentioning
confidence: 99%
“…Insufficient maternal GWG may harm an infant’s neurodevelopment, according to a large survey conducted in Japan in 2021 ( 32 ). GWG below recommended levels was linked to a significantly higher risk of developmental delay for the domains of communication (odds ratio [OR] 1.21, 95% confidence interval [CI] 1.09–1.34), gross motor (OR 1.14, 95%CI, 1.05–1.24), fine motor (OR 1.13, 95%CI, 1.04–1.24), problem-solving (OR 1.09, 95%CI, 1.01–1.18), and personal-social (OR 1.15, 95%CI, 1.08–1.25) ( 32 ). Contrary to these research, a correlation between maternal obesity or overweight and a child’s cognitive development was not found in two cohorts of European infants at around 3 years of age ( 32 , 33 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Women with higher pre-pregnancy BMI may be likely to gain more weight during pregnancy than indicators issued by Institute of Medicine (IOM) guidelines [ 50 ]. We lack data on GWG, which is also associated with children’s neurodevelopment [ 51 ]. Meanwhile, the C-ABCS was the first cohort we have established in Anhui province, we did not collect maternal waist circumference and other measures of body fat.…”
Section: Discussionmentioning
confidence: 99%